Downtown Mardi Gras : New Carnival Practices in Post-Katrina New Orleans - Wade, Leslie A.; De Caro, F. A., 1943-2020; Roberts, Robin, 1957- (Book collections on Project MUSE., 2019)
"After Hurricane Katrina devastated New Orleans and the surrounding region in 2005, the city debated whether to press on with Mardi Gras or cancel the parades. Ultimately, they decided to proceed. New Orleans's recovery certainly has resulted from a complex of factors, but the city's unique cultural life--perhaps its greatest capital--has been instrumental in bringing the city back from the brink of extinction. Voicing a civic fervor, local writer Chris Rose spoke for the importance of Carnival when he argued to carry on with the celebration of Mardi Gras following Katrina: "We are still New Orleans. We are the soul of America. We embody the triumph of the human spirit. Hell, we ARE Mardi Gras." Since 2006, a number of new Mardi Gras practices have gained prominence. The new parade organizations or krewes, as they are called, interpret and revise the city's Carnival traditions but bring innovative practices to Mardi Gras. The history of each parade reveals the convergence of race, class, age, and gender dynamics in these new Carnival organizations. Downtown Mardi Gras: New Carnival Practices in Post-Katrina New Orleans examines six unique, offbeat, Downtown celebrations. Using ethnography, folklore, cultural, and performance studies, the authors analyze new Mardi Gras's connection to traditional Mardi Gras. The narrative of each krewe's development is fascinating and unique, illustrating participants' shared desire to contribute to New Orleans's rich and vibrant culture."--Provided by publisher.